Gaya Kepemimpinan Yonas Howay Dalam Meningkatkan Elektabilitas Partai Demokrat Kota Sorong Pada Pileg 2019 - Purnomo, Arie; Pangala, Fadhir; Ali, Muhammad; Nurjanah, Siti (Universitas Muhammadiyah Sorong, 2023)
This research aims to determine Yonas Howay's leadership style in increasing the electability of the Sorong City Democratic Party in the 2019 Legislative Election and the obstacles that hinder Yonas Howay's efforts to increase the electability of the Sorong City Democratic Party. This research was conducted in Sorong City, Southwest Papua using a descriptive qualitative approach where data collection techniques used observation, interviews, documentation. The data analysis used is qualitative, namely in the form of data reduction, data presentation, drawing conclusions and verification. The results of the research show that Yonas Howay's leadership style is a democratic leadership style where democratic decisions are made in an open atmosphere which is the result of deliberation and consensus so that it is not felt as coercion and his efforts are to increase the electability of the party by socializing with the community and distributing basic necessities to less fortunate people. Meanwhile, the obstacles in increasing the electability of the Democratic Party are the lack of leadership assertiveness, emotional closeness and financial capability.